A numerical study of microtube geometry effect on flow boiling using the volume of fluid method. (15th December 2022) - Lin, Chia-Wei; Lin, Yu-Chen; Kumar, Ranjith; Lin, Ming-Chieh; Hsu, Hua-Yi
Highlights: The microtube geometry effect on flow boiling has been studied by VOF. The shortened divergent microtube increases the heat flux up to 38713.1 W/m 2 and reduce the down to 214.24 Pa. The total pressure drop in the divergent microtube is the lowest. The shorter divergent microtube obtains a higher heat flux with G=560 kg/m 2 s. Convergent microtube results in the higher heat flux with the highest pressure drops. Abstract: Other than pursuing high heat flux, pressure drop also plays a key role in microtube applications as the power and efficiency of a pump are determined in terms of pressure drop. In the literature, only a few studies focus on how tube geometry influences pressure drop. This study numerically investigates the geometry effect on microtube flow boiling and pressure drop using the volume of fluid (VOF) method. Three types of geometries are used in this study: divergent, normal, and convergent microtubes with different lengths and hydraulic diameter ratios. The transient developments of vapor formation, heat flux, and pressure drops are presented within 200 ms. It is shown that the total pressure drop in the divergent microtube is the lowest. The heat flux is decreased as the massive vapor bubbles clog the tube. However, the shortened divergent microtube can increase the heat flux up to 38713.1 W/m 2 and reduce the pressure drop down to 214.24 Pa, compared to the normal one under certain flow conditions, while the tube-clogging effect is not dominant. A larger inflow mass flux can delay the vapor bubble formation on the heated wall, which is beneficial to prevent the tube clogging and leads to a higher heat flux. On the other hand, higher heat flux can be achieved in the convergent microtube due to the increasing velocity inside the tube, although it induces the highest total pressure drop. This study provides a better fundamental understanding of the microtube geometry effect on flow boiling and relevant physical insight for the future design of microscale heat transfer applications.